Comparison of the prognosis of bisphosphonate-related osteonecrosis of the jaw caused by oral and intravenous bisphosphonates. Issue 7 (July 2015) - Shintani, T.; Hayashido, Y.; Mukasa, H.; Akagi, E.; Hoshino, M.; Ishida, Y.; Hamana, T.; Okamoto, K.; Kanda, T.; Koizumi, K.; Yoshioka, Y.; Tani, R.; et al.
Abstract Bisphosphonates (BPs) have been used in medical practice for the treatment of osteoporosis, bone metastasis, and multiple myeloma. Although many studies have been published, the treatment and prognosis of bisphosphonate-related osteonecrosis of the jaw (BRONJ) remain unclear. This study included 59 patients with BRONJ: 29 had taken oral BPs and 30 had taken intravenous (IV) BPs. All received conservative treatments. When separated sequestra were seen, a sequestrectomy was performed. Segmental mandibular resection was performed when pathological fractures were diagnosed. The outcomes of treatments were compared between groups. For patients treated with oral rinses or mandibular resection, the number in whom clinical healing was observed did not differ between the oral BP and IV BP groups. With regard to sequestrectomy, 94% of patients in the oral BP group showed improvement with this treatment compared to 50% in the IV BP group. The number of patients in whom clinical healing of BRONJ was achieved was statistically better in the oral BP group than in the IV BP group after 6 months of treatment (P < 0.001). The results showed that >90% of patients treated with oral BPs could be cured. However, 50% of patients treated with IV BPs did not show an improvement. Additional research is needed to further increase the therapeutic efficacy for the resolution of BRONJ.